Case Report: COVID-19 Pandemic Exacerbates Eating Disorder by Social and Intrafamilial Isolation - Katsumi, Yoshiki; Kodo, Kazuki; Goto, Sachiko (Frontiers in Pediatrics, 2022)
The coronavirus disease-2019 (COVID-19) pandemic has increased the stress levels of children and their parents; and diagnoses of eating disorders (EDs), irritable bowel syndrome, migraines, tension headaches, orthostatic dysregulation, and/or school refusal has increased among children. We present the case of a nine, which rapidly worsened due to stress and isolation related to the COVID-19 pandemic. The patient’s father noted her rapid weight loss due to poor oral intake. While she had already stopped gaining weight before the pandemic, her weight rapidly decreased to 22 kg during the pandemic. We diagnosed her with an ED and administrated nasogastric tube feeding. We postulated that not only social isolation, but also the disruption in her relationship with her parents, due to the pandemic, contributed to her ED. During a family meeting, she revealed that she felt more anxious during the pandemic. After the meeting, her parents rescheduled their jobs so that the family can have dinner together every night. The patient started eating sufficiently, and weighed 31.8 kg at the one-year follow-up. The proportion of children with ED increased during the pandemic; their symptoms worsened because they felt lonely due to social and intrafamilial isolation. While parents have themselves experienced more stress during the pandemic, children, including those with ED, have experienced increased stress directly related to the pandemic, as well as indirectly from their parents. Pediatricians should consider the impact of stress on children, especially from social and intrafamilial isolation ,both during and after the pandemic.